Eye complications of cetuximab therapy - Melichar, B; Nemcová, I (European journal of cancer care, 2007)
Skin toxicity is the most important side effect of cetuximab administration, but little is known about the eye toxicity, including periorbital skin. We present here four cases of patients with metastatic colorectal carcinoma treated with the combination of cetuximab, irinotecan, 5-fluorouracil and leucovorin who had manifestation of complications in the eye or periorbital skin. These manifestations consisted of erythematous eruptions in the periorbital skin with blepharitis and conjunctivitis in three patients and trichomegaly in one patient. The symptoms were controlled with local therapy including corticosteroids and antibiotics. The skin toxicity in the periorbital region is more important than in other skin areas because of the impact on the social activity of the patient and the vision. The manifestations of eye toxicity of cetuximab may be controlled by local therapy, and the management of these patients requires the collaboration of medical oncologist and ophthalmologist.
Keywords: Humans; Drug Eruptions; cetuximab; lidé středního věku; Antibodies, Monoclonal; Female; dospělí; Antineoplastic Agents; Cetuximab; výsledek terapie; léková dermatitida; lidé; humanizované monoklonální protilátky; oční nemoci; Adult; Neoplasm Metastasis; Antibodies, Monoclonal, Humanized; metastázy nádorů; ženské pohlaví; kolorektální nádory; Male; Middle Aged; Treatment Outcome; monoklonální protilátky; protinádorové látky; Eye Diseases; mužské pohlaví; Colorectal Neoplasms